Quarterly Letter: The Best Safety Value - Walter Rosser and Jan Kasperski (Healthcare Quarterly, 2001)
HealthcarePapers has hit another home run! I read your latest journal "Making Patients Safer! Reducing Error in Canadian Healthcare" (Vol. 2 No. 1) cover to cover. I enjoyed it immensely; however, you forgot to ask a family doctor to contribute to the dialogue.